The impact of labor mobility restrictions on managerial actions: Evidence from the mutual fund industry - Gjergji Cici; Mario Hendriock; Alexander Kempf (University of Cologne, Centre for Financial Research (CFR), 2018)
This paper examines how labor mobility restrictions such as non-compete clauses in employment contracts affect the incentives and resulting behavior of employees. Using the investment industry as a testing laboratory, we find that mutual fund managers respond to heightened career concerns due to increased enforceability of non-compete clauses by increasing effort, reducing downside risk, engaging less in tournaments, making their portfolios similar to the portfolios of their benchmarks or peers, and increasing window-dressing. These concerns are, however, moderated by the presence of more developed internal labor markets, which allow managers to substitute restricted across-family mobility with within-family mobility.
Keywords: 330